Evectivity Of Acupressure Therapy For Premenstrual Syndrome Pain In Adolescent Girls At Al Azhar Paya Jeget Pegasing Integrated Boarding School, Central Aceh Regency - Ainun, Kamaliah; Kristina, Kristina (Sean Institute, 2024)
Premenstrual syndrome (PMS) occurs a few days before menstruation and even until menstruation takes place. WHO prevalence of productive women experienced PMS of 53.87% and 56.19%). In Indonesia, 90% of women of reproductive age experience PMS symptoms. Non-pharmacological management, including Acupressure, is a form of physiotherapy by providing massage and stimulation at certain points on the body. The purpose of the study was to determine the effectiveness of acupressure therapy on premenstrual pain syndrome. The research design uses sectional croos, which is a study that is conducted at one time, there is no repetition, the population in this study is adolescent girls. The sampling technique was Simple Random with a total of 34 people, data presentation was carried out univariate and bivariate, using a single sample test. The results of the study were measured by Visual Analog Scale (VAS). With the results of the pre-therapy pain scale of Acupressure in the mild category of 25 (73.5%), while the post pain scale was carried out in the category of no pain 22 (64.7%), with a Sign value of (0.000) ≤ 0.05 which indicates that there is an effect of acupressure therapy on the premenstrual pain scale. The study concludes that there is an effectiveness between acupressure therapy and the premenstrual pain scale. Suggestions that this acupressure therapy can be used as a therapy to relieve pain during Premenstruation. It is hoped that the respondents will be applied this Acupressure therapy in overcoming premenstrual pain.